On the spectrum and spacetime supersymmetry of heterotic ambitwistor string - Flores, Henrique [UNESP]; Lize, Matheus [UNESP] (Springer, 2019)
We analyse the BRST cohomology of the Ramond sector of heterotic ambitwistor theory. We also write the free string field theory action and compute the supersymmetry transformations.
Keywords: BRST Quantization; String Field Theory; Superstrings and Heterotic Strings